2015
DOI: 10.1371/journal.pone.0131008
|View full text |Cite
|
Sign up to set email alerts
|

Nisin ZP, a Bacteriocin and Food Preservative, Inhibits Head and Neck Cancer Tumorigenesis and Prolongs Survival

Abstract: The use of small antimicrobial peptides or bacteriocins, like nisin, to treat cancer is a new approach that holds great promise. Nisin exemplifies this new approach because it has been used safely in humans for many years as a food preservative, and recent laboratory studies support its anti-tumor potential in head and neck cancer. Previously, we showed that nisin (2.5%, low content) has antitumor potential in head and neck squamous cell carcinoma (HNSCC) in vitro and in vivo. The current studies explored a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(131 citation statements)
references
References 57 publications
5
120
1
5
Order By: Relevance
“…This result is in accordance with previous studies on HaCaT cells, however, performed with Nisin Z . Our result contradicts findings from a previous study, where Nisin A was cytotoxic against HUVEC where 50% of the cells died at 100 μg/ml …”
Section: Discussionsupporting
confidence: 89%
“…This result is in accordance with previous studies on HaCaT cells, however, performed with Nisin Z . Our result contradicts findings from a previous study, where Nisin A was cytotoxic against HUVEC where 50% of the cells died at 100 μg/ml …”
Section: Discussionsupporting
confidence: 89%
“…; Kamarajan et al . ). For example, nisin has beneficial properties in the context of biomedical applications, including bacterial infections, cancer, oral diseases and more.…”
Section: Nisin: a Bacterially Derived Antimicrobialmentioning
confidence: 97%
“…) (Kamarajan et al . ). Considering that the FDA has approved 83·25 mg kg −1 in humans as the no‐observed‐effect‐level for nisin (66·7 mg kg −1 was used in mice as a cancer therapeutic dose), this study demonstrated the promising potential for nisin as an anticancer agent.…”
Section: Bacteriocins and Cancer: Nisin As A Cancer Therapeuticmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, with demonstrated safety over the past 40 years, the use of nisin has expanded into a diverse array of applications, including those related to the biomedical industry . Many lantibiotics possess additional biological activities beyond their antimicrobial activities . Therefore, nisin has beneficial properties in the context of biomedical applications, including bacterial infections, cancer, immune modulation, oral diseases, and more.…”
Section: A Unique Probiotic Nisin‐producing Lactococcus Lactismentioning
confidence: 99%